ANALISIS METODE DAN AKURASI ARAH KIBLAT MASJID DI KECAMATAN PITU RIAWA KABUPATEN SIDRAP - Andi Wawo Warah; Rahmatiah HL (HISABUNA: Jurnal Ilmu Falak, 2020)
The direction of Qibla becomes one of the legitimate requirements of prayer worship which is obligatory for Islamic Ummah, based on the word of Allah Swt on QS. Al-Baqarah/2:144, QS. Al-Baqarah/2:145, and QS. Al-Baqarah/2:150, and there are also some hadith that narrated in relation to the direction of Qibla namely at HR. Bukhari, hr. Baihaqi, and also several opinions of scholars such as Imam Shafi'i, Maliki, Hanbali and Imam Hanafi. The orders facing the Qiblah make the ummah of Islam pay attention to the initial position when it will carry out the Saalat, so it is necessary to make qibla direction for the mosque which becomes the place of prayer for Muslims. Then it is considered necessary to re-check the position of Qibla direction Mosque in Pitu Riawa district of Kab. Sidrap with a total of 10 villages, However, the samples used only 5 mosques that can be an overview of the Qibla direction position located in the sub-district of Riawa, based on the method of measurement performed and the level of accuracy of qibla direction of the mosque by testing directly to the field using the instrument Qiblat Tracker as one of the qibla direction measurement instruments. Thus, it is found that the accuracy of the mosque in Pitu Riawa sub-district is still not accurate because the results of the measurements there are more than 7 degrees more than a few, there are even more than the from. Five mosques that have been measured can be the benchmark for the remaining five mosques that have not been tested in Pitu Riawa Kabupaten Sidrap Sub-district.